How do family members experience drug death bereavement? A systematic review of the literature. Issue 7 (9th August 2021) - Titlestad, Kristine Berg; Lindeman, Sari Kaarina; Lund, Hans; Dyregrov, Kari
Abstract: Despite high rates of drug-related deaths (DRDs), drug-related bereavement has been sparsely investigated. A systematic literature search for qualitative and quantitative studies was conducted. Studies on bereaved DRD family members and systems influencing bereavement were eligible for inclusion. Eight studies were included. Three themes emerged from the thematic analysis (Emotional Roller Coaster, Lack of Understanding by the Social World, and Meaning Making) describing an emotional and existential overload, stigmatization and lack of understanding and help from support systems. The results also shed light on life after the loss. Directions for further research were subsequently outlined.